What is an adequate living wage level for South Africa? - Pather, Kimaya (School of Management Studies, 2025)
The study presented in this dissertation had three aims: To determine what an adequate living wage level for South Africa would be, to assess the differences between provinces when looking at quality of life (QoL) and income and what the implications arising from this would be for a national living wage, and lastly, to compare Teng-Calleja et al's (2021) and Botha's (2021) QoL formulae. The study follows on from prior research conducted with data from two separate, geographically confined South African samples collected in 2015 and 2019. Like in this prior research, it argues that a subjective approach, rather than an objective, econometric approach is required to determine a relevant living wage level for South Africa and that Sen's Capability Model presents an adequate theoretical framework for this. A living wage is thus understood as the wage level from which onwards it becomes possible for individuals to have choice over the areas of life which matter to them, meaning that they have acquired the capabilities they desire. Having such choice – or capabilities realised - is equated to a good QoL. The research differs from previous studies in that it is based on a large, nationally diverse sample with participants residing in all nine South African provinces (N=1,015) and utilises both Teng-Calleja's and Botha's QoL formulae, allowing for comparison. Data was collected in late 2022 and early 2023. In this cross-sectional, exploratory, and descriptive survey study QoL was determined as the degree to which individuals perceived their valued capabilities to be realised. Two approaches to calculating QoL were employed in the analysis. QoL was plotted against individuals' self-reported income levels using a local polynomial regression (locally estimated scatterplot smoothing or LOESS). The results showed that both methods led to similar results. A monthly living wage of at least R10,000 – R11,000 would allow South Africans to achieve a good QoL. In the provincial analyses, Western Cape, Eastern Cape, and Gauteng reported the highest average incomes and Free State, Limpopo, and North West reported the lower average incomes in the sample. Provincial LOESS curves produced living wage amounts which varied greatly by province, ranging from R5,000 – R22,000 per month. Results showed that Mpumalanga, Western Cape, and Limpopo would require the lowest monthly incomes to achieve a decent QoL, followed by Eastern Cape, KwaZulu-Natal, Free State, Gauteng, and again Western Cape which produced the largest required income range to achieve a good QoL, ranging from R8,000 – R22,000. Lastly, Teng-Calleja's and Botha's formulae for calculating QoL produced nearly identical results. These results provide employers who aim to pay a living wage with a benchmark amount, and advocates for living wages can use the benchmark to inform living wage policy.